Heterogeneity of Persistence of Salmonella enterica Serotype Senftenberg Strains Could Explain the Emergence of this Serotype in Poultry Flocks - Boumart, Zineb; Roche, Sylvie M.; Lalande, Françoise; Virlogeux-Payant, Isabelle; Hennequet-Antier, Christelle; Menanteau, Pierrette; Gabriel, Irène; Weill, François-Xavier; Velge, Philippe; Chemaly, Marianne (PLOS ONE, 2012)
Salmonella enterica serotype Senftenberg (S. Senftenberg) has recently become more frequent in poultry flocks. Moreover some strains have been implicated in severe clinical cases. To explain the causes of this emergence in farm animals, 134 S. Senftenberg isolates from hatcheries, poultry farms and human clinical cases were analyzed. Persistent and non-persistent strains were identified in chicks. The non-persistent strains disappeared from ceca a few weeks post inoculation. This lack of persistence could be related to the disappearance of this serotype from poultry farms in the past. In contrast, persistent S. Senftenberg strains induced an intestinal asymptomatic carrier state in chicks similar to S. Enteritidis, but a weaker systemic infection than S. Enteritidis in chicks and mice. An in vitro analysis showed that the low infectivity of S. Senftenberg is in part related to its low capacity to invade enterocytes and thus to translocate the intestinal barrier. The higher capacity of persistent than non-persistent strains to colonize and persist in the ceca of chickens could explain the increased persistence of S. Senftenberg in poultry flocks. This trait might thus present a human health risk as these bacteria could be present in animals before slaughter and during food processing.